If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying k + -49 = -62 Reorder the terms: -49 + k = -62 Solving -49 + k = -62 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '49' to each side of the equation. -49 + 49 + k = -62 + 49 Combine like terms: -49 + 49 = 0 0 + k = -62 + 49 k = -62 + 49 Combine like terms: -62 + 49 = -13 k = -13 Simplifying k = -13
| 13-7x=88-42x | | (x)(6)=-30 | | 19-2x=5-10x | | -14t+7=49 | | -11.1x=77.7 | | 4x-f=-22 | | x-8.1=-3.7 | | -9(3b+2)+(28b-2)=0 | | -5-4+q=12 | | p^3+7p-6=0 | | 4s^2+8s=221 | | 5.3q-1.7-5.5q=-1.29-3.6 | | 2611x+622=126 | | 6y-15=y | | 23=3y+5 | | 223-5x=40x+18 | | 7y=3y+8 | | 11+x=5 | | 11.7=w+16.8 | | x-47=-46 | | 4(x+7)=50 | | 126-3x=33x+22 | | 100x-5=90x | | 4a+2a=6a | | 2x+5=35-4x | | 14b-24=-2b+8 | | 9-10x=66-31x | | 9m+14=-12m | | y=2x^2-11x | | -52-9x=8x+15 | | 233-5x=40x+23 | | 35n^2-195n-350=0 |